IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES IN ORGANIZING CONTINUOUS LAW EDUCATION - Bakhodir Bakhtiyorovich Sadullaev (Scholar Express Journal, 2022)
This article describes the main aspects of the problem and the right of education and the formation of the legal culture of youth in the process of continuing education. The article indicated by the funds necessary for the development of the legal culture. The article below discusses the methodology and theory of education of law in non-low specialized higher educational institutions
Keywords: young students; the system of continuous education; secondary schools; vocational colleges